2021
DOI: 10.20473/jhpr.vol.4-issue.1.1-7
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF GELATIN AND GLUTARALDEHYDE CONCENTRATIONS ON CHARACTERISTICS OF CANTIGI (Vaccinium Varingiaefolium Miq.) EXTRACT LOADED GELATIN NANOPARTICLES AS ANTIOXIDANT

Abstract: Cantigi is an endemic plant of sub-alpine area of Mount Tangkuban Parahu in Bandung, Indonesia. Previous study showed ethanol extract of young red leaves had antioxidant activity, however no information on this activity if changed into nanoparticles. The purpose of this study was to determine the effects of gelatin and glutaraldehyde concentrations on the characteristics of Cantigi extract loaded gelatin nanoparticles and to evaluate the antioxidant activity of nanoparticles. Cantigi leaves were extracted by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
1
9
0
2
Order By: Relevance
“…Figure 1 shows the morphology of Cantigi extract-loaded gelatin nanoparticles enlarged 3000 times using SEM. It was spherical and consistent with the previous report (Kosasih et al, 2019). This is the first report on the antiageing activities of Cantigi leaf extracts and gelatin nanoparticles loaded with the extracts.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 1 shows the morphology of Cantigi extract-loaded gelatin nanoparticles enlarged 3000 times using SEM. It was spherical and consistent with the previous report (Kosasih et al, 2019). This is the first report on the antiageing activities of Cantigi leaf extracts and gelatin nanoparticles loaded with the extracts.…”
Section: Resultssupporting
confidence: 92%
“…In general, all evaluated parameters met the standards (Ditjen POM RI, 2000). Table II (A) shows the formula of Cantigi extract-loaded gelatin nanoparticles used in the study based on previous reports (Khan, 2014;Kosasih et al, 2019). The study in 2019 used ethanol extract as the active ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…The empirical uses of Cantigi are antiinflammatory, antispasmolytic, and antihypertensive. A previous study showed that Cantigi extract has a very potent antioxidant activity (IC50 <20 ppm) (Kosasih et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research that has been conducted on phytochemical screening shows that cantigi leaves contain phytochemical compounds such as anthocyanins, chlorophyll, phenols, saponins, steroids, tannins, triterpenoids, and flavonoids (5) . Previous research showed cantigi leaves extract has antioxidant activity and an IC 50 of 16.84 ppm, which is categorized as having very strong antioxidant activity (6). Therefore, to obtain standardized cantigi leaf extract (Vaccinium varingaefolium Miq.…”
Section: Introductionmentioning
confidence: 99%